History, Hagiography and Religious Works: The Writings of William of Malmesbury and his Date of Birth - Ming Liu (Tabularia)
By reconsidering the two dominating opinions about his date of birth, this paper argues that William of Malmesbury, the famous Anglo-Norman historian, was born in c. 1091, probably late that year. It also explores the chronology of William’s different works, reconciling the problems and contradictions raised by previous scholarship. It opens further discussion of the boundaries between history, hagiography and religious works in his writings, as well as offering a detailed insight into a monastic author’s understanding of the genres of writing in the early-twelfth-century Anglo-Norman world.